Pengaruh Pengungkapan CSR, Karakter Eksekutif, Profitabilitas, Dan Investasi Aktiva Tetap Terhadap Penghindaran Pajak - Merkusiwati, Ni Ketut Lely Aryani; Eka Damayanthi, I Gst Ayu (E-Jurnal Akuntansi; Vol 29 No 2 (2019)DO - 10.24843/EJA.2019.v29.i02.p26, 2019)
Tax avoidance is one way to reduce the amount of tax legally that does not violate tax regulations, in contrast to tax evasion, which uses unlawful methods to reduce or eliminate the tax burden while tax avoidance (tax avoidance) ) utilizing loopholes in tax regulations to avoid paying larger amounts of tax. This study was conducted to determine the effect of Corporate Social Responsibility (CSR), executive character, profitability and investment in fixed assets in tax avoidance. This research was conducted at manufacturing companies listed on the Indonesia Stock Exchange in 2015-2017. Sampling using a purposive sampling technique. The data analysis technique used in this study is multiple linear regression. Regression test results show that CSR and executive character negatively affect tax avoidance. while the profitability and investment of fixed assets have no effect on tax avoidance. Keywords : CSR; Executive Character; Profitabilitas; Capital Intensity; Tax Avoidance.